Short Communication: Genetic diversity of Salacca edulis from West Seram District, Maluku, Indonesia based on morphological characters and RAPD profiles - SOVIAN SESCA ELLY; THEOPILUS W. WATUGULY; DOMINGGUS RUMAHLATU (Biodiversitas Journal of Biological Diversity, 2018)
Elly SS, Watuguly TW, Rumahlatu D. 2018. Short Communication: Genetic diversity of Salacca edulis from West Seram District, Maluku, Indonesia based on morphological characters and RAPD profiles. Biodiversitas 19: 1777-1782. Morphological and RAPD-based genetic diversity analyses of Salacca edulis Reinw populations from West Seram District were performed. A survey was conducted in four locations in the village of Riring, Rumahsoal, Taniwel, Neniari, and Soya. Forty-two morphological characters and three RAPD primer were used. Data were analyzed on the NTSys program version 2.0 to perform UPGMA clustering analysis. An UPGMA dendrogram based on morphological characters resulted in two main groups with similarity value varied from 0.46-0.75 for morphology and 0.35-0.89 for RAPD. The result gives us important about cultivar of Salacca edulis in West Seram District Maluku which has high genetic diversity and germplasm. These results and can be used for further research for conservation as native cultivar.